2014
DOI: 10.1039/c4an00479e
|View full text |Cite
|
Sign up to set email alerts
|

A chitosan-Au-hyperbranched polyester nanoparticles-based antifouling immunosensor for sensitive detection of carcinoembryonic antigen

Abstract: Analysts are always interested in finding new functional nanomaterials and devices with good properties for electrochemical sensor applications. In this paper, hyperbranched polyester nanoparticles with carboxylic acid functional groups (HBPE-CA NPs) were synthesized and combined with chitosan wrapped around Au nanoparticles (CS-Au NPs) to prepare a novel and sensitive electrochemical immunosensor by adsorption of carcinoembryonic antibody (anti-CEA) on the (HBPE-CA)/CS-Au NPs modified glass carbon electrode (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2017
2017
2025
2025

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 23 publications
(3 citation statements)
references
References 49 publications
0
3
0
Order By: Relevance
“…It is noteworthy to mention that hybrid nanoparticles and nanosystems 27,28 are not exclusively needed for biology and medicine, green chemistry, 29 sensor technology, 30 and other fields; additionally, these are also favorable for the advent of novel potent analytical procedures 31 which worthy of overcoming problems of identification and detection of impurities, 32 poor water solubility, 33 immunogenicity, 34 low bioavailability, high toxicity, 35 etc. Analysis of various research articles dedicated to hybrid nanoparticles revealed that the horizon of their application is often designated by the qualities of one of the components 36 . Other components either increase the functional abilities in the same area or elevate the overall system efficiency.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is noteworthy to mention that hybrid nanoparticles and nanosystems 27,28 are not exclusively needed for biology and medicine, green chemistry, 29 sensor technology, 30 and other fields; additionally, these are also favorable for the advent of novel potent analytical procedures 31 which worthy of overcoming problems of identification and detection of impurities, 32 poor water solubility, 33 immunogenicity, 34 low bioavailability, high toxicity, 35 etc. Analysis of various research articles dedicated to hybrid nanoparticles revealed that the horizon of their application is often designated by the qualities of one of the components 36 . Other components either increase the functional abilities in the same area or elevate the overall system efficiency.…”
Section: Introductionmentioning
confidence: 99%
“…Analysis of various research articles dedicated to hybrid nanoparticles revealed that the horizon of their application is often designated by the qualities of one of the components. 36 Other components either increase the functional abilities in the same area or elevate the overall system efficiency. Nanostructures having magnetic nanoparticles can be manipulated by an outer magnetic field, which is employed as contrast agents 37 in targeted drug delivery 38,39 or for magnetic resonance imaging (MRI); whereas hybrid nanoparticles based on magnetic nanoparticles 40 along with the incorporation of luminescent nanostructures 39 can be used to envision the specific site of delivery.…”
mentioning
confidence: 99%
“…26 A electrochemical sensor with carboxymethyl-PEG-carboxymethyl (CM-PEG-CM) and a thrombin-binding aptamer (TBA) was reported to detect thrombin with a detection range of 1 pM to 160 nM and a detection limit of 1.56 Â 10 À14 M. 27 Furthermore, an electrochemical immunosensor that used adsorption of carcinoembryonic antibody (anti-CEA) on hyperbranched polyester nanoparticles with carboxylic acid functional groups (HBPE-CA)/Au NPs was developed, which presented an excellent signal response to carcinoembryonic antigen (CEA) with a detection range of 1-107 fg mL À1 and a detection limit of 0.251 fg mL À1 . 28 Therefore, electrochemical immunosensors can rapidly and conveniently detect their target analyte with high sensitivity in a broad linear range and have a low detection limit. Inspired by the merits of electrochemical immunosensors, aer the successful preparation of a HEX monoclonal antibody, a novel HEX monoclonal antibody/MACA/nanogold electrochemical immunosensor was constructed in this work to detect four phenolic oestrogens (HEX, DES, DE and BPA) by a design strategy involving a nanosized effect, layer by layer selfassembly and antigen-antibody specic immune technology.…”
Section: Introductionmentioning
confidence: 99%